1999
DOI: 10.1111/j.1365-2621.1999.tb12271.x
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Crispness and Crunchiness of Roasted Hazelnuts and Correlations with Sensory Assessment

Abstract: Crispness and crunchiness of 15 samples of roasted hazelnuts were investigated. Force deformation curves from compression cell testing were analyzed and mechanical response variables were determined for roasted hazelnuts. Regression equations based on roasting air temperature, air velocity, and roasting time explained (R 2 5 0.9 -0.98, p < 0.001) the mechanical response variables. Samples were also evaluated by a quantitative descriptive panel. Among the mechanical response variables, the first fracture point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 11 publications
5
47
0
4
Order By: Relevance
“…The results of structure descriptors of roasted hazelnuts were similar to those obtained by Saklar et al (1999).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of structure descriptors of roasted hazelnuts were similar to those obtained by Saklar et al (1999).…”
Section: Discussionsupporting
confidence: 74%
“…After the preliminary training session, according to Saklar et al (1999), Alasalvar (2003Alasalvar ( , 2012, Vázquez-Araújo (2011), Bett-Garber (2012), and Suwonsichon (2012) 18 specific sensory descriptors were chosen besides the overall judgment ( Table 2). The hazelnut samples were presented to the tasters in small glasses (Valentini et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The fracture force of samples changed from 25.54-82 N. These results are in agreement with those found by Saklar et al (1999) for roasting hazelnuts, Dogan and Cronin (2004) for roasting hazelnuts and Nikzadeh and Sedaghat (2008) for roasting pistachio nuts. They generally reported that during the roasting of nuts, fracture force was decreased.…”
Section: Fracture Forcesupporting
confidence: 81%
“…However, the panelists preferred the softer kernels (Table 4). Decrease in peak force at compression test was in relation to increase in sensory scores for various roasted oilseeds (Saklar et al 1999;Varela et al 2008;Wanlapa and Jindal 2006;McDaniel et al 2012). Effect of other factors on hardness of roasted kernels were not significant (P > 0.05).…”
Section: Pistachio Kernelsmentioning
confidence: 87%
See 1 more Smart Citation